Diatom of the Bacillariophyceae Class in Thermophilic Microbial Mats Present in Sulphurous Hot Springs and their Possible Biotechnological Application - Puy-Alquiza, María Jesús; Luna, Berenice Noriega; Miranda-Aviles, Raúl; Hernández, Ma. Mercedes Salazar; Aguilera, Gilberto Carreño (Global Journal of Earth Science and Engineering, 2021)
The diversity of diatoms in the hot springs of the Comanjilla geothermal zone in northern Guanajuato, Mexico was studied. Hot springs are extreme ecosystems that, despite having high temperatures, constitute an environment for many thermophilic microorganisms (bacteria, cyanobacteria, and diatoms). The thermal water studied is classified as hyperthermal water (45°C to 100°C), of deep origin, and with low mineralization, are of type sulfuric sodium chloride, since the dissolved content of hydrogen sulfide (H2S) is found in concentrations higher than 1mg/L, and its smell is similar to the one of rotten eggs, presents a pH of 7.6 to 9.1 that represents neutrophilic to alkaliphilic environments, with a variable electrical conductivity (EC) (658-698 µs / cm) and total dissolved solids (TDS) (314-24 ppm). In the same way, these hot springs present microbial mats that consist of several stratified layers of green and orange color of 100 cm2, each one, which are dominated by specific types of microorganisms such as bacteria, cyanobacteria, but mainly diatoms, the latter were studied applying the scanning electron microscope and the optical microscope. The morphological characteristics observed in the optical microscope and in the scanning electron microscopy indicate the presence of diatoms of the Bacillariophyceae class, represented by Sellaphora disjuncta (55%), Achnanthes brevipes var. intermedia (45%). This diatom present in thermophilic microbial mats in the sulphurous geothermal zone of Comanjilla represents: a) the first report of said microorganisms in the study area and Mexico; b) an ecosystem of great interest from the biotechnological and industrial point of view; c) an important taxon in terms of diversity and technology; d) an applications in biofuels, environmental monitoring, wastewater treatment, manufacture of fertilizers, production of secondary metabolites, medical compounds, energy sources and food industry and within nanotechnology. It is important to mention that the physical and chemical characteristics of thermal water such as temperature, pH, dissolved solids, electrical conductivity, hardness, alkalinity and silica concentrations, were the major environmental factors influencing the distribution of diatoms in sulphurous hot springs.